Fermentation of hydrogen, 1, 3-propanediol and ethanol from glycerol as affected by organic loading rate using up-flow anaerobic sludge blanket (UASB) reactor. (9th November 2017) - Sittijunda, Sureewan; Reungsang, Alissara
Abstract: The influences of organic loading rate (OLR) on the production of biohydrogen, 1, 3-propanediol (1, 3-PD) and ethanol from glycerol in an up-flow anaerobic sludge blanket (UASB) by anaerobic mixed cultures were investigated. UASB reactor was firstly operated using pure glycerol as the substrate at various OLRs of 25, 37.5, 50, 62.5 g/L d. Results showed that a change in OLR led to a change in hydrogen production, hydrogen production rate (HPR), hydrogen yield (HY), 1, 3-PD and ethanol production as well as glycerol consumption, and microbial community. The optimal OLR for hydrogen and ethanol production was found to be 50 g/L d when the UASB was fed with pure glycerol, while the optimal OLR for 1, 3-PD production was 62.5 g/L d. After the optimum OLR was obtained, the reactor was fed with crude glycerol. Maximum hydrogen, ethanol and 1, 3-PD production from crude glycerol was obtained at the same OLR as of pure glycerol. A maximum hydrogen production, HY, ethanol and 1, 3-PD production of 134.2 mmol/L, 579.8 mmol H2 /mol glycerol, 78.9 mmol/L and 60.9 mmol/L, respectively, were obtained when pure glycerol was used as the substrate. However, when crude glycerol was used as the substrate, a maximum hydrogen production, HY, ethanol and 1, 3-PD production were lower than that of using pure glycerol as the substrate. Analysis of microbial community by polymerase chain reaction-denaturing gradient gel electrophoresis indicated that the predominant hydrogen producers at the optimum OLR of 50 g/L d, when crude glycerol was used as the substrate, were Clostridium sp., Enterobacter sp., uncultured Firmicutes bacterium, and uncultured Actinobacterium while Enterobacter sp., Klebsiella sp., were the predominant 1, 3-PD producers and Clostridium sp., as well as Enterobacter sp., were the predominant ethanol producers. Graphical abstract: Highlights: Hydrogen, 1, 3-PD and ethanol production from crude glycerol was conducted. HY, 1, 3-PD and EtOH of 368 mmol H2 /mol glycerol, 55 and 71 mmol/L were obtained. The optimum OLRs was 50 g/L d using waste glycerol as the substrate. Total energy conversion efficiency of 63.63% was obtained.